Core–shell-like Au sub-nanometer clusters in Er-implanted silica. Issue 19 (21st May 2015) - Maurizio, Chiara; Cesca, Tiziana; Perotto, Giovanni; Kalinic, Boris; Michieli, Niccolò; Scian, Carlo; Joly, Yves; Battaglin, Giancarlo; Mazzoldi, Paolo; Mattei, Giovanni
<x xml:space="preserve">Abstract</x> The very early steps of Au metal cluster formation in Er-doped silica have been investigated by high-energy resolution fluorescence-detected X-ray absorption spectroscopy (HERFD-XAS).